STUDI LITERATUR MENGENAI PERAN NPV DAN IRR DALAM PENILAIAN KELAYAKAN PROYEK INVESTASI PADA SEKTOR UMKM - Christian Damar Sagara Sitepu; Dini Annisa Putri; Farah Karar; Umi Juli Handayani; Aulia Wildaniah; Abiyyah Suha (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze investment feasibility in Micro, Small, and Medium Enterprises (MSMEs) through a literature review approach using two primary methods: Net Present Value (NPV) and Internal Rate of Return (IRR). The analysis is conducted by reviewing five previous studies that applied both methods to various MSME sectors. The findings show that four MSMEs—the vegetable farming business, Laga Lagi Thrift, Cokelat Cozy, and medicinal plant cultivation—obtained positive NPV values and IRR levels exceeding the discount rate, indicating financial feasibility. In contrast, the Sate Taichan Kitee MSME recorded a negative NPV and an IRR below the cost of capital, making the investment financially unfeasible. This study highlights that NPV and IRR are effective instruments for evaluating investment profitability and risk in MSMEs. The combined use of both methods provides a comprehensive foundation for rational and data-driven investment decision-making.